Alterations in Mitochondrial and Endoplasmic Reticulum Signaling by p53 Mutants - Giorgi, Carlotta; Bonora, Massimo; Missiroli, Sonia; Morganti, Claudia; Morciano, Giampaolo; Wieckowski, Mariusz R.; Pinton, Paolo (Frontiers in Oncology, 2016)
The p53 protein is probably the most important tumor suppressor, acting as a nuclear transcription factor primarily through the modulation of cell death. However, currently, it is well accepted that p53 can also exert important transcription-independent pro-cell death actions. Indeed, cytosolic localization of endogenous wild-type or trans-activation-deficient p53 is necessary and sufficient for the induction of apoptosis and autophagy. Here, we present the extra-nuclear activities of p53 associated with the mitochondria and the endoplasmic reticulum (ER), highlighting the activities of the p53 mutants on these compartments. These two intracellular organelles play crucial roles in the regulation of cell death, and it is now well established that they also represent sites where p53 can accumulate.